Rhodian amphora stamps found in Mleiha (Sharjah, UAE): old and recent finds. (11th October 2013) - Monsieur, Patrick; Overlaet, Bruno; Jasim, Sabah A.; Yousif, Eisa; Haerinck, Ernie
<x xml:space="preserve">Abstract</x> To date Mleiha has yielded eighteen stamps belonging to Rhodian wine amphorae. Eleven of these can be dated to the second half of the third and the first half of the second centuries BC. Rhodian stamps are vital for the chronological framework of the PIR‐A period at Mleiha. Most of them, if not all, belonged to funerary contexts but were unfortunately rarely found in undisturbed contexts. The stamp types of the eponym Ἀριστεύς and of the fabricants Ἀπολλώνιος and Φιλοστέφανος do not seem to occur very often.